The Impact of Public Holidays on Insurgent Attacks: The Case of Thailand - Chinda, Chris (Terrorism and political violence, 2024)
This paper analyzes Malay-Muslim insurgents’ attacks in the three southern provinces of Thailand between the years of 2010–2021 and identifies the role of public holidays on the level of violence. The existing literature suggests terrorists consider holidays during attack planning. However, there is a lack of agreement on the effect direction. Some studies have found that holidays are a force for peace while others have found they can act as trigger for more violence. Applying environmental criminology to the timing of terrorist attacks, we argue that the type of the holiday matters. Therefore, we analyze public (secular), Islamic, and Buddhist holidays separately. We show that Islamic holidays witness increased violence while Buddhist and public holidays see reductions. We discuss that Islamic holidays increase the Malay-Muslim insurgents’ motivation to attack by assigning to those dates a higher symbolic value. On the other hand, on Buddhist and public holidays, insurgents may hesitate to attack to avoid the adverse effects of losing public support and triggering a backlash. The results demonstrate the necessity to analyze the temporal dynamics of terrorist attacks.